Two-Photon Antenna-Core Oxygen Probe with Enhanced Performance - Roussakis, Emmanuel (American Chemical Society, 2014)
[Image: see text] Recent development of two-photon phosphorescence lifetime microscopy (2PLM) of oxygen enabled first noninvasive high-resolution measurements of tissue oxygenation in vivo in 3D, providing valuable physiological information. The so far developed two-photon-enhanced phosphorescent probes comprise antenna-core constructs, in which two-photon absorbing chromophores (antenna) capture and channel excitation energy to a phosphorescent core (metalloporphyrin) via intramolecular excitation energy transfer (EET). These probes allowed demonstration of the methods’ potential; however, they suffer from a number of limitations, such as partial loss of emissivity to competing triplet state deactivation pathways (e.g., electron transfer) and suboptimal sensitivity to oxygen, thereby limiting spatial and temporal resolution of the method. Here we present a new probe, PtTCHP-C307, designed to overcome these limitations. The key improvements include significant increase in the phosphorescence quantum yield, higher efficiency of the antenna-core energy transfer, minimized quenching of the phosphorescence by electron transfer and increased signal dynamic range. For the same excitation flux, the new probe is able to produce up to 6-fold higher signal output than previously reported molecules. Performance of PtTCHP-C307 was demonstrated in vivo in pO(2) measurements through the intact mouse skull into the bone marrow, where all blood cells are made from hematopoietic stem cells.